Ending “Too Big To Fail”: Government Promises Versus Investor Perceptions - Gormley, Todd A.; Johnson, Simon; Rhee, Changyong (Review of Finance, 2015)
Abstract Can a government credibly promise not to bailout firms whose failure would have major negative systemic consequences? Our analysis of Korea’s 1997–98 crisis suggests an answer: No. Despite a general “no bailout” policy during the crisis, the largest Korean corporate groups—facing severe financial and governance problems—could still borrow heavily from households by issuing bonds at prices implying very low expected default risk. The evidence suggests “too big to fail” beliefs were not eliminated by government promises because investors believed that this policy was not time consistent. Subsequent bailouts confirmed the market view that creditors would be protected.